Sharia Transformations Cultural Politics and the Rebranding of an Islamic Judiciary - Peletz, Michael G. (University of California Press, 2020)
Few symbols in today's world are as laden and fraught as sharia--an Arabic-origin term referring to the straight path, the path God revealed for humans, the norms and rules guiding Muslims on that path, and Islamic law and normativity as enshrined in sacred texts or formal statute. Yet the ways in which Muslim men and women experience the myriad dimensions of sharia often go unnoticed and unpublicized. So too do recent historical changes in sharia judiciaries and contemporary strategies on the part of political and religious elites, social engineers, and brand stewards to shape, solidify, and